Hikikomori Phenomenon in East Asia: Regional Perspectives, Challenges, and Opportunities for Social Health Agencies - Wong, John Chee Meng; Wan, Michelle Jing Si; Kroneman, Leoniek; Kato, Takahiro A.; Lo, T. Wing; Wong, Paul Wai-Ching; Chan, Gloria Hongyee (Frontiers in Psychiatry, 2019)
Hikikomori, first originating in Japan, refers to the condition where youths withdraw into the home and do not participate in society for an extended period of time. Recent updates on hikikomori presentation within the region were exchanged at a Hikikomori Round Table and Regional Symposium (HRTRS) discussion late 2017, leading to this perspective paper. Hikikomori presents as an overall homogeneous construct, while diversity in clinical presentation exist across East Asian countries. We overview the various presentations, risk factors, theoretical frameworks and classification issues about hikikomori. In particular, specific risk factors have emerged to some degree across the region, while some are more locale specific. We propose that hikikomori youths have differential onset and developmental patterns, potentially resulting in heterogeneous presentation. We briefly summarize existing interventions in the East Asian region. Intervention strategies need to be tailored to different subtypes. A multi-component approach would address complexity, multifactorial onset and development of the condition. The HRTRS presented participating countries the opportunity to collectively work towards a more universal definition of the hikikomori condition and explore innovative ways to shape existing service structures. Opportunities for participating countries described pertain to early detection of cases, adoption of assessment tools and improved intervention services.